Optimizing the antimicrobial efficacy of dental poly (methyl methacrylate) through Al2O3 atomic layer deposition - Leite, Lady Daiane P. [UNESP]; Júnior, William Chiappim [UNESP]; Pessoa, Rodrigo S.; Koga-Ito, Cristiane Y. [UNESP] (Springer Nature, 2025)
Poly(methyl methacrylate) (PMMA) is extensively used in dentistry for its aesthetics, processability, and affordability, but its susceptibility to Candida albicans contributes to denture stomatitis. This study explores atomic layer deposition (ALD) of aluminum oxide (Al2O3) as a post-fabrication strategy to suppress fungal colonization without altering PMMA bulk properties. PMMA discs were coated with 250–3000 ALD cycles (12.5–150 nm) and characterized by SEM/EDS, FTIR, and water contact angle; antifungal activity was assessed after 24 h with C. albicans ATCC 18804. Thin coatings (12.5–25 nm) increased hydrophobicity (73 → 88°), reduced surface free energy (~ 20 mJ m⁻2), and maintained nanoroughness < 10 nm, lowering fungal counts by 50% (p < 0.01). Thicker films (≥ 50 nm) developed microcracks, restoring surface energy and fungal adhesion. Thus, an optimal ALD window (12.5–25 nm) was identified where defect-free Al2O3 nanofilms effectively halve colonization, representing a promising route to extend PMMA prosthesis lifespan and reduce biofilm-related infections.Graphical abstract